PEMBUATAN ALAT SHUTTLE RUN DENGAN DATA TERSIMPAN PADA DATABASE BERBASIS ARDUINO - Yohandri Yohandri; Kurnia Ashadi (Jurnal Sosioteknologi, 2021)
Athletes require agility as a fundamental skill. A shuttle run is one method for assessing an athlete’s agility. The aim ofthis research is to design and develop a shuttle run instrument with recorded data based on Arduino. This shuttle runinstrument is used to assess a person’s speed and endurance, with the results being saved in a database and then sentto a website. Engineering research method is adopted in this research. In this instrument, an Arduino is programmedas a timer to calculate an athlete’s running time, which is controlled by sensors. The photodiode sensor detects athletespassing through the shuttle, and the ESP8266 module connects Arduino to the database. The data collected by theArduino is saved in a database and is accessible via the internet. The accuracy and precision of the timer of shuttlerun instrument is investigated. Ten students took part in the test to evaluate shuttle run instrument’s performance.Measured result shows the accuracy and precision of the instruments is obtained 80.8% and 99.5%, respectively.Based on measured result, the shuttle run instrument is accurate and precision for operating in agility assessment.